The five wounds : a novel - Quade, Kirstin Valdez (W.W. Norton & Company, 2021)
"From an award-winning storyteller comes a stunning debut novel following a New Mexican family's extraordinary year of love and sacrifice. It's Holy Week in the small town of Las Penas, New Mexico, and thirty-three-year-old unemployed Amadeo Padilla has been given the part of Jesus in the Good Friday procession. He is preparing feverishly for this role when his fifteen-year-old daughter Angel shows up pregnant on his doorstep and disrupts his plans. Their reunion sets her own life down a startling path. Vivid, tender, darkly funny, and beautifully rendered, The Five Wounds spans the baby's first year as five generations of the Padilla family converge: Amadeo's mother, Yolanda, reeling from a recent discovery; Angel's mother, whom Angel isn't speaking to; and disapproving Tio Tive, keeper of the family's history. In the absorbing, realist tradition of Elizabeth Strout and Jonathan Franzen, Kirstin Valdez Quade conjures characters that will linger long after the final page, bringing to life their struggles to parent children they may not be equipped to save"--